2022
DOI: 10.1115/1.4055032
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Biomechanics: Concepts, Bone as Prominent Example, and Perspectives Beyond

Abstract: Biological materials and systems are hierarchically organized.The main motivation for hierarchical biomechanics is that the wide variability of mechanical properties encountered at the macroscopic scale may be traced back to just a few universal. i.e. tissue-invariant, mechanical properties of elementary components at a sufficiently small scale (such as collagen, elastin, and water in case of soft tissues; complemented by hydroxyapatite in case of hard tissues), and to the nano and microstructures which the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 277 publications
0
7
0
Order By: Relevance
“…Furthermore, in this study, we only consider a single MCF and do not consider other components of the ultrastructural arrangement. In particular, the extrafibrillar matrix and non-collagenous proteins, which are shown to significantly affect the bone mechanical properties [40][41][42][43]76,77], have not been considered. Several other studies have explicitly considered the important role of extrafibrillar mineralization on the effective properties of the tissue [40][41][42][43][44], and these have shown excellent agreement with experimental observations in the elastic regime.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in this study, we only consider a single MCF and do not consider other components of the ultrastructural arrangement. In particular, the extrafibrillar matrix and non-collagenous proteins, which are shown to significantly affect the bone mechanical properties [40][41][42][43]76,77], have not been considered. Several other studies have explicitly considered the important role of extrafibrillar mineralization on the effective properties of the tissue [40][41][42][43][44], and these have shown excellent agreement with experimental observations in the elastic regime.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the extrafibrillar matrix and non-collagenous proteins, which are shown to significantly affect the bone mechanical properties [40][41][42][43]76,77], have not been considered. Several other studies have explicitly considered the important role of extrafibrillar mineralization on the effective properties of the tissue [40][41][42][43][44], and these have shown excellent agreement with experimental observations in the elastic regime. However, the model presented here is an idealized MCF model, which is more difficult to validate as it cannot be physically isolated from the tissue in the absence of an extrafibrillar mineral.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that this process is influenced by the following main factors: (1) cell shrinkage, leading to cytoskeleton rearrangement in response to applied mechanical stimuli; 29 (2) ECM properties, 30 such as matrix stiffness and matrix roughness of the surface; and (3) the spatiotemporal characteristics of the applied stimulus 31,32 . Previous research has indicated that mechanical loading is applied and measured based on the consideration of length scale‐related factors 33 . Mechanical stress, whether defined as the force per unit area in a one‐dimensional analysis or through the Cauchy stress tensor in a three‐dimensional context, is highly dependent on the size of the area being measured.…”
Section: Discussionmentioning
confidence: 99%
“…The highly oriented apatite crystals grown on the DD surface in the presence of the peptide-CS hydrogels formed a robust mineralized layer with organized structures, dictating its mechanical strength (Hellmich et al 2022). The newly formed apatitic layer bound tightly to the remineralized dentin and could withstand rigorous ultrasonication challenges.…”
Section: Discussionmentioning
confidence: 99%